Comparison of average daily gain, apparent digestibility, rumen fermentation parameters and bacterial communities, and serum antioxidant indices in Leizhou goats fed with or without rumen-protected fat - Liu, Hu; Mao, Hongxiang; Wang, Wenji; Peng, Weishi; Mao, Kaiyu; Sun, Wei; Yang, Yuanting; Wu, Qun; Wang, Ke; Zeng, Meng; Han, Jiancheng; Zhou, Hanlin (Frontiers in Veterinary Science, 2024)
IntroductionRumen-protected fat (RPF) is a vital dietary energy source for dairy cows. However, the influences of RPF on rumen volatile fatty acid (VFA) content and bacterial communities in goats are poorly documented.MethodsIn this study, 12 castrated male goats (body weight [BW]: 13.3 ± 0.02 kg; 6 months of age) were used as the experimental animal and then allocated into two groups (n = 6): a control group, fed a basal diet without RPF supplementation, and the RPF supplementation group, fed a basal diet with 2.4% RPF supplementation.ResultsThe final BW and ADG were higher (p < 0.05) and the ratio of dry matter (DM) intake to ADG was lower (p < 0.05) in the 2.4% RPF supplementation group compared with those in the control group. The 2.4% RPF supplementation group showed a higher total tract digestibility of DM, CP, OM, neutral and acid detergent fiber compared with that of the control group (p < 0.05). The proportion of acetate was higher (p < 0.05) and that of propionate was lower (p < 0.05) in the 2.4% RPF supplementation group compared with those in the control group. The relative abundances of Christensenellaceae_R-7_group, unclassified_f__Selenomonadaceae, norank_f__Selenomonadaceae, Quinella, norank_f__Bacteroidales_RF16_group, and unclassified_o__Bacteroidales were higher (p < 0.05) and those of Lachnospiraceae_NK3A20_group, norank_f__F082, Olsenella, Erysipelatoclostridiaceae_UCG-004, and Syntrophococcus were lower (p < 0.05) in the 2.4% RPF supplementation group compared with those in the control group.DiscussionIn conclusion, 2.4% RPF supplementation can improve the ADG and antioxidant capacity by regulating the rumen bacterial communities and enhancing the apparent total tract digestibility in growing Leizhou goats.